2017
DOI: 10.1038/s41598-017-09049-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sources and sinks of dissolved inorganic carbon across Swedish streams, refocusing the lens of stable C isotopes

Abstract: It is well established that stream dissolved inorganic carbon (DIC) fluxes play a central role in the global C cycle, yet the sources of stream DIC remain to a large extent unresolved. Here, we explore large-scale patterns in δ13C-DIC from streams across Sweden to separate and further quantify the sources and sinks of stream DIC. We found that stream DIC is governed by a variety of sources and sinks including biogenic and geogenic sources, CO2 evasion, as well as in-stream processes. Although soil respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
137
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 77 publications
7
137
0
Order By: Relevance
“…This fraction of the DIC is largely geogenic, which basically reflects regional geology, and since there is only a weak relation between regional geology and the major ecoregions in terms of NPP and climate, this may indicate that much of the gaseous form of DIC (CO 2 ) is biogenic in origin. The use of δ 13 C isotopes would help discriminate these sources, for example, Campeau, Wallin, et al () showed that DIC in Swedish streams was mainly biogenic in origin using δ 13 C‐DIC.…”
Section: Discussionmentioning
confidence: 99%
“…This fraction of the DIC is largely geogenic, which basically reflects regional geology, and since there is only a weak relation between regional geology and the major ecoregions in terms of NPP and climate, this may indicate that much of the gaseous form of DIC (CO 2 ) is biogenic in origin. The use of δ 13 C isotopes would help discriminate these sources, for example, Campeau, Wallin, et al () showed that DIC in Swedish streams was mainly biogenic in origin using δ 13 C‐DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study show that ambient δ 13 C‐DIC was universally enriched relative to respiratory δ 13 C‐DIC (Figure a). This suggests that either the initial pore or rainwater DIC was enriched or it started as the depleted product of soil respiration and became fractionated during downstream transport (Campeau et al, ). We suggest that CO 2 off‐gassing may have fractionated the DIC pool, since DIC concentrations significantly decreased downstream (Figure a), while ambient δ 13 C‐DIC became more enriched (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this application can be complicated by the presence of additional biogeochemical transformations influencing the observed δ 13 C‐DIC values. The influence of CO 2 evasion on δ 13 C‐DIC values has been documented in soils (Amundson et al, ; Cerling et al, ; Davidson, ), larger river systems (Giesler et al, ; Hélie et al, ; Voss et al, ), and headwater streams (Amiotte‐Suchet et al, ; Doctor et al, ; van Geldern et al, ), but it is likely that the patterns in δ 13 C‐DIC values simultaneously reflect a larger range of sources and processes (Campeau, Wallin, et al, ).…”
Section: Introductionmentioning
confidence: 99%